Galaxy and Mass Assembly (GAMA): variation in galaxy structure across the green valley. Issue 3 (14th April 2018) - Kelvin, Lee S; Bremer, Malcolm N; Phillipps, Steven; James, Philip A; Davies, Luke J M; De Propris, Roberto; Moffett, Amanda J; Percival, Susan M; Baldry, Ivan K; Collins, Chris A; Alpaslan, Mehmet; Bland-Hawthorn, Joss; et al.
Abstract: Using a sample of 472 local Universe ( z  < 0.06) galaxies in the stellar mass range $10.25\, \, {<}\, \, \log \boldsymbol {\mathcal {M}}_{\star }/\boldsymbol {\mathcal {M}}_{{\odot }}\, \, {<}\, \, 10.75$, we explore the variation in galaxy structure as a function of morphology and galaxy colour. Our sample of galaxies is subdivided into red, green, and blue colour groups and into elliptical and non-elliptical (disk-type) morphologies. Using Kilo-Degree Survey (KiDS) and Visible and Infrared Survey Telescope for Astronomy (VISTA) Kilo-Degree Infrared Galaxy Survey (VIKING) derived postage stamp images, a group of eight volunteers visually classified bars, rings, morphological lenses, tidal streams, shells, and signs of merger activity for all systems. We find a significant surplus of rings (2.3σ) and lenses (2.9σ) in disk-type galaxies as they transition across the green valley. Combined, this implies a joint ring/lens green valley surplus significance of 3.3σ relative to equivalent disk-types within either the blue cloud or the red sequence. We recover a bar fraction of ${\sim }44\hbox{ per cent}$ which remains flat with colour, however, we find that the presence of a bar acts to modulate the incidence of rings and (to a lesser extent) lenses, with rings in barred disk-type galaxies more common by ∼20–30 percentage points relative to their unbarred counterparts, regardless of colour. Additionally, green valley disk-type galaxies with a bar exhibit a significant 3.0σ surplus of lenses relative to their blue/red analogues. The existence of such structures rules out violent transformative events as the primary end-of-life evolutionary mechanism, with a more passive scenario the favoured candidate for the majority of galaxies rapidly transitioning across the green valley.